Schaum's Anatomy and Physiology Problem 2.17: Describe how biochemical compounds are formed and broken down. - Copppinger, J. Peter (McGraw-Hill's AccessEngineering., 2013)
This video outlines the chemical reactions involved in building and breaking down the four macromolecules found in living cells.